Estrategias metodológicas para mejorar la dislexia en los niños y niñas el séptimo grado en la asignatura de Lengua y Literatura, bloque 6 la historieta de la escuela de educación general básica “Rosa Grimaneza Ortega” de la parroquia El Sagrario, cantón y provincia de Loja, periodo académico 2014-2015 - Zhigui Torres, Ximena Belen (2015)
This research titled STRATEGIES METHODOLOGICAL TO IMPROVE DYSLEXIA IN THE BOYS AND GIRLS IN THE SEVENTH GRADE IN THE SUBJECT OF LANGUAGE AND LITERATURE, BLOCK 6 THE CARTOON OF THE SCHOOL OF EDUCATION GENERAL BASIC "ROSA GRIMANEZA ORTEGA" OF THE PARISH THE TABERNACLE,CANTON AND PROVINCE OF LOJA, ACADEMIC PERIOD 2014-2015 , have as general objective to applying methodological strategies for children with dyslexia that allows them to improve learning in the subject of language and literature, block six the cartoon, this research is preexperimental. The following methods were used: comprehensive, analytical, synthetic, scientific were used as instruments the questionnaire, the techniques of direct observation and the application of a survey of a teacher and 20 students to get the information and develop this research was used. Isobtained as a result that students know what is dyslexia and have difficulty reading and writing, so it is concluded that the application of methodological strategies by the method of the workshop, directly benefiting students and teachers, helping to improve the difficulties students have in learning through reading comprehension and cartoons shown by Pearson's r. Therefore recommend that teachers makeuse of strategies, techniques and methods to meet the educational needs of their students and to contribute to the development of meaningful learning